Dead-ends and Secure Exploration in Reinforcement Learning - Fatemi, Mehdi; Sharma, Shikhar; van Seijen, Harm; Kahou, Samira Ebrahimi (Proceedings of the 36th International Conference on Machine Learning (ICML), 2019)
Many interesting applications of reinforcement learning (RL) involve MDPs that include many "dead-end" states. Upon reaching a dead-end state, the agent continues to interact with the environment in a dead-end trajectory before reaching a terminal state, but cannot collect any positive reward, regardless of whatever actions are chosen by the agent. The situation is even worse when existence of many dead-end states is coupled with distant positive rewards from any initial state (it is called Bridge Effect). Hence, conventional exploration techniques often incur prohibitively large training steps before convergence. To deal with the bridge effect, we propose a condition for exploration, called security. We next establish formal results that translate the security condition into the learning problem of an auxiliary value function. This new value function is used to cap "any" given exploration policy and is guaranteed to make it secure. As a special case, we use this theory and introduce secure random-walk. We next extend our results to the deep RL settings by identifying and addressing two main challenges that arise. Finally, we empirically compare secure random-walk with standard benchmarks in two sets of experiments including the Atari game of Montezuma's Revenge.